Urokinase-type plasminogen activator is effective in fibrin clearance in the absence of its receptor or tissue-type plasminogen activator. - Bugge, T H (1996)
The availability of gene-targeted mice deficient in the urokinase-type plasminogen activator (uPA), urokinase receptor (uPAR), tissue-type plasminogen activator (tPA), and plasminogen permits a critical, genetic-based analysis of the physiological and pathological roles of the two mammalian plasminogen activators. We report a comparative study of animals with individual and combined deficits in uPAR and tPA and show that these proteins are complementary fibrinolytic factors in mice. Sinusoidal fibrin deposits are found within the livers of nearly all adult mice examined with a dual deficiency in uPAR and tPA, whereas fibrin deposits are never found in livers collected from animals lacking uPAR and rarely detected in animals lacking tPA alone. This is the first demonstration that uPAR has a physiological role in fibrinolysis. However, uPAR-/-/tPA-/- mice do not develop the pervasive, multi-organ fibrin deposits, severe tissue damage, reduced fertility, and high morbidity and mortality observed in mice with a combined deficiency in tPA and the uPAR ligand, uPA. Furthermore, uPAR-/-/tPA-/- mice do not exhibit the profound impairment in wound repair seen in uPA-/-/tPA-/- mice when they are challenged with a full-thickness skin incision. These results indicate that plasminogen activation focused at the cell surface by uPAR is important in fibrin surveillance in the liver, but that uPA supplies sufficient fibrinolytic potential to clear fibrin deposits from most tissues and support wound healing without the benefit of either uPAR or tPA.